UPAYA INDONESIA DALAM MENGIMPOR VAKSIN DARI INDIA PADA TAHUN 2019-2022 - Sephia Marsha Tiara Dinda Lofa; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Covid-19 is an infectious disease caused by the SARS-CoV2 virus which can irritate the respiratory tract. Since Covid-19 has been declared a global pandemic. Various policies have been formulated to deal with this pandemic, one of which is the vaccination program. This study aims to find out and analyze the efforts made by Indonesia in importing the Covovax vaccine produced by India during the Covid-19 period. This research will also discuss what efforts have been made by Indonesia to be able to obtain the vaccine so that it can be used and distributed evenly among all Indonesian people. This study uses qualitative research methods, with data collection techniques through literature studies sourced from several books, journals, articles, and also websites. This research also uses the perspective of neoliberalism, the level of analysis of the nation state, and also uses the theory of diplomacy to further strengthen this research. The research results prove that the success of Indonesia's efforts to import the covovax vaccine from India started with a meeting of the Indian delegation discussing the potential for cooperation between the two countries, then the Indonesian government made a joint agreement, and finally resolved the joint problem. The results of Indonesia's efforts to import the covavax vaccine from India in 2019-2022 were declared successful, this can be seen from the implementation, namely: 1) Indonesia and India entered into a vaccine agreement, 2) Prepared a vaccine budget. 3) Conducting vaccine negotiations/diplomacy, 4) Importing vaccines, and 5) Indonesia conducting licensing or the legality of the covovax vaccine. Keywords: International Health Cooperation, Covid-19Vaccine Import, India-Indonesia